DETERMINAN KINERJA PERBANKAN: STUDI EMPIRIS PADA BANK DI INDONESIA - Krismi Budi Sienatra (Universitas Bunda Mulia, 2020)
Bank performance is determined by many factors such as internal and external factors. This study aims to investigate the determinants of banking performance in Indonesia. By using samples from banks at the Indonesia Stock Exchange during the period 2013-2016 with a total of 32 banks. Internal factor variables used in this study include company size, capital ratios, deposit ratios, loan ratios, and non-performing loan ratios and banking performance using proxy return on assets and return on equity. The results of the study using linear regression analysis shows the results of the firm size ratio, capital ratio and non-performing loan ratio have an influence on profitability while the deposit ratio and lending ratio do not have an influence on bank performance either return on assets or return on equity.